(untitled) (Global Journal of Management and Business Research, 2018)
The main aim of this research is to discover the factor that influences job satisfaction and the factors that can help improve it. Especially, demographic and environmental factors are given the most importance. The present research is designed with a clear view to find out the satisfaction level of academic staff of different education institute at Dhaka city corporation area. Therefore, the intent of this research is to examine the factors that influence job satisfaction of employees in educational sector. The research is quantified in its nature with a sample size of 100 employees from different education institute at Dhaka City Corporation area. The respective data are analyzed with descriptive statistics, correlation and multiple regressions. And the respective results are interpreted and the conclusion is drawn on the basis of the data analysis.